2021
DOI: 10.1155/2021/6661107
|View full text |Cite
|
Sign up to set email alerts
|

Deterioration of Physical and Mechanical Properties of Rocks by Cyclic Drying and Wetting

Abstract: Both surface and underground rocks in nature often undergo repeated drying and wetting. The dry-wet cycle is a weathering effect that includes physical and chemical processes, which has varying degrees of degradation effects on the physical and mechanical properties of rocks. This paper analyzes and discusses this kind of rock degradation based on the existing literature data. First, the deterioration degree of various physical and mechanical properties (including density, P-wave velocity, porosity, static and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 93 publications
0
7
0
Order By: Relevance
“…According to several studies on the damage caused by rising damp in the presence of salts [39,40], porous stone materials are particularly damaged, with a reduction in mechanical strength and an increase in porosity.…”
Section: Discussionmentioning
confidence: 99%
“…According to several studies on the damage caused by rising damp in the presence of salts [39,40], porous stone materials are particularly damaged, with a reduction in mechanical strength and an increase in porosity.…”
Section: Discussionmentioning
confidence: 99%
“…There is the obvious chromatic effect (wetter materials are darker), but physical disruption with consequent erosion has also been ascribed to wetting-drying cycles. Several publications have attempted to relate the evolution of rocks' properties to wetting-drying cycles, and a recent review can be found in Zhang et al [44].…”
Section: Wettingmentioning
confidence: 99%
“…Kunyou Zhou et al [17] analyzed experimentally the mechanical behavior of coal samples in saturation with water and demonstrated that with the increase in water saturation, the uniaxial compression strength and the elastic modulus reduced, while Poisson's ratio grew. Zhizhen Zhang et al [18] arrived at a conclusion that with the increased number of wetting-drying cycles, the mechanical properties of rocks (argillite) degraded.…”
Section: Introductionmentioning
confidence: 99%